Selametan and Mubeng Asem: Acculturation between Islamic Teaching and Javanese Tradition in Pati, Central Java - Rohman, Taufiqur; Azizah, Balkis Nur; Dlifa'in, Alif Faza; Ramadhan, Mahendra Utama Cahya (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
Pre-wedding traditions have become an inseparable point in wedding traditions among the Javanese community. This research aims to explores the Mubeng Asem tradition in Kuryokalangan village, Gabus, Pati, Central Java, which is deeply rooted in local customs and Islamic principles. This research uses a qualitative descriptive approach, using observation, interviews, and documentation to combine data. The results show that the Mubeng Asem tradition represents Javanese ancestors’ efforts to maintain harmony in the household and protect the Kuryokalangan community. The tradition primarily involves expressing gratitude to the family as family members enter the marriage phase, symbolizing the family’s gratitude and upholding Eastern cultural norms.